Fingertip replantation using artery-only anastomosis: case series - Giri, Piyush; Pokhrel, Shrinkhala; Pandey, Pratishtha; Kunwar, Sushma; Khadka, Karuna (Journal of Patan Academy of Health Sciences, 2024)
The fingertip is a complex organ compacted with precise functional roles of fine movements and fine touch sensory functions. Fingertip injury commonly occurs in machinery work, and presents as crush injuries or amputations. Even though it is a challenging procedure due to the area of injury relative to the size of vessels for restoration, fingertip replantation has been developing as a newer method for both functional and aesthetic restoration, with better success rates and improved long-term outcomes. Artery-only replant has been emerging as a suitable option in many cases, which allows the blood to flow out of the injury site, allowing the natural venous revascularization, owing to the difficulty in small venous anastomosis. Here, we present two cases with fingertip replantation using artery-only anastomosis who underwent fingertip replantation at Tamai level II without venous anastomosis.